DNA Methylation in Pediatric Obstructive Sleep Apnea: An Overview of Preliminary Findings - Perikleous, Evanthia; Steiropoulos, Paschalis; Tzouvelekis, Argyris; Nena, Evangelia; Koffa, Maria; Paraskakis, Emmanouil (Frontiers in Pediatrics, 2018)
Obstructive sleep apnea (OSA) is characterized by phenotypic variations, which can be partly attributed to specific gene polymorphisms. Recent studies have focused on the role of epigenetic mechanisms in order to permit a more precise perception about clinical phenotyping and targeted therapies. The aim of this review was to synthesize the current state of knowledge on the relation between DNA methylation patterns and the development of pediatric OSA, in light of the apparent limited literature in the field. We performed an electronic search in PubMed, EMBASE, and Google Scholar databases, including all types of articles written in English until January 2017. Literature was apparently scarce; only 2 studies on pediatric populations and 3 animal studies were identified. Forkhead Box P3 (FOXP3) DNA methylation levels were associated with inflammatory biomarkers and serum lipids. Hypermethylation of the core promoter region of endothelial Nitric Oxide Synthase (eNOS) gene in OSA children were related with decreased eNOS expression. Additionally, increased expression of genes encoding pro-oxidant enzymes and decreased expression of genes encoding anti-oxidant enzymes suggested that disturbances in oxygen homeostasis throughout neonatal period predetermined increased hypoxic sensing in adulthood. In conclusion, epigenetic modifications may be crucial in pediatric sleep disorders to enable in-depth understanding of genotype-phenotype interactions and lead to risk assessment. Epigenome-wide association studies are urgently needed to validate certain epigenetic alterations as reliable, novel biomarkers for the molecular prognosis and diagnosis of OSA patients with high risk of end-organ morbidity.